Efektifitas Jus Stroberi dan Pisang Ambon terhadap Kadar Hemoglobin pada Ibu Hamil - Sari, Dewi Kartika; Eva Dianing A; Sudriman (Kabar Gizi Indonesia, 2024)
Anemia is a common disorder that often occurs during pregnancy. It is a condition in which the body has a lower number of red blood cells (erythrocytes) than required. A preliminary survey in Blitar Regency in October 2023 found that out of 10 pregnant women with anemia, 4 individuals (40%) showed a high incidence of anemia. The aim of this study is to determine the effectiveness of strawberry juice and Ambon banana on hemoglobin levels in pregnant women. The statistical test using paired T-Test showed that there is an influence of strawberry juice on hemoglobin levels in pregnant women with a p-value of 0.002. There is an influence of Ambon banana on hemoglobin levels in pregnant women with a p-value of 0.000. The Independent Sample T-Test with a p-value of 0.038 and α = 0.05. With the positive effects of both strawberry juice and Ambon banana, they can be used as daily food to increase hemoglobin levels.